FEA Modelling of a Novel Tubular Linear Generator - Eugene, Joseph; Lewis, Clive; Riley, Chris; Dalchau, Neil; Michaelides, Alex (Linear Drives for Industrial Applications, 2007)
This paper presents the finite element modelling of a novel tubular linear generator, designed for efficient wave energy conversion. The paper presents generator design considerations to meet the demands of the intended application. In addition, the paper concentrates on novel aspects of generator modelling using electromagnetic finite element analysis, which were adopted to fully characterise the generator performance at the development stage, hence alleviating the need for prototyping, the cost of which was unacceptable for this application.